A structural study of the self-association of different starches in presence of bacterial cellulose fibrils. (15th July 2022) - Díaz-Calderón, P.; Simone, E.; Tyler, A.I.I.; Enrione, J.; Foster, T.
Abstract: A multi-analytical study was performed to analyse the effect of bacterial cellulose (BCF) on the self-association of starches with different amylose content (wheat, waxy-maize), assessing macrostructural properties (rheology, gel strength) and some nano and sub-nano level features (small and wide-angle X-ray scattering). Although pasting viscosities and G′ were significantly increased by BCF in both starches, cellulose did not seem to promote the self-association of amylose in short-range retrogradation. A less elastic structure was reflected by a 2–3-fold increase in loss factor (G″/G′) at the highest BCF concentration tested. This behavior agreed with the nano and sub-nano characterisation of the samples, which showed loss of starch lamellarity and incomplete full recovery of an ordered structure after storage at 4 °C for 24 h. The gel strength data could be explained by the contribution of BCF to the mechanical response of the sample. The information gained in this work is relevant for tuning the structure of tailored starch-cellulose composites.